2019
DOI: 10.3855/jidc.11295
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and quality of life among HIV positive injection drug users in Ukraine, 2017

Abstract: Introduction: People who inject drugs (PWID) are one of the key populations most vulnerable to HIV infection, with 28 times higher prevalence compared to the rest of the population. PWID are known to have many physical, psychological and lifestyle challenges that can influence access to care. Depression is common among PWID living with HIV. It has major effect on health-related quality of life (HRQoL) and is influencing adherence to antiretroviral therapy. This study was conducted to explore how anxiety and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…In recent studies from Ukraine, the prevalence of selfreported depression among PWID as measured by CES-D and Hospital Anxiety and Depression Scale has been high, up to 60%, which is similar to our findings [16,17]. Among PLWH in Ukraine, the prevalence of depression was 25% [18] compared with 12% in the general population [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In recent studies from Ukraine, the prevalence of selfreported depression among PWID as measured by CES-D and Hospital Anxiety and Depression Scale has been high, up to 60%, which is similar to our findings [16,17]. Among PLWH in Ukraine, the prevalence of depression was 25% [18] compared with 12% in the general population [19].…”
Section: Discussionsupporting
confidence: 89%
“…In Vietnam, daily injections were more common among respondents with depression in a previous study [4], but, among HIV outpatients in Vietnam, drug use was not associated with depressive symptoms [53]. Similarly, in Ukraine, depressive symptoms were not associated with frequency of injection [16,54]. In contrast, in Indonesia, depressive symptoms have been associated with recent substance use [5].…”
Section: Discussionmentioning
confidence: 83%
“…Approximately one in five patients in our study reported depressive symptoms, lower than the rate of 47% among PLHIV in a pooled meta-analysis from middle-income countries [40]. The QoL scores in our study were also more favorable than those observed in a recent study focused on HIV-positive PWID in Ukraine, for both physical health (47 vs. 43) and mental health (44 vs. 35) [45]. That the PRO scores in our study were not as unfavorable as observed in other studies might be explained by the fact that participants in our study were active on ART and the majority had achieved viral suppression.…”
Section: Adherencecontrasting
confidence: 56%
“…QOL is an important outcome indicator of HIV treatment. Compared with the general population, HIV-infected patients have lower quality of life due to life-long medications, suffering from side effects and anxiety/depression [ 2 , 3 ]. A meta-analysis of 9,000 people living with HIV/AIDS (PLWHA) found that nearly 58% of HIV-infected persons have a high degree of sleep disturbance, and those with sleep disturbance also show more depression and health problems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the quality of life of HIV-infected patients is lower than that of people in general [ 3 ], there is no research discussing the relationship between TCM constitution and quality of life in HIV-infected patients. This study explores the correlation between the distribution of HIV-infected MSM patients in TCM constitution and quality of life in Taiwan, and what type of constitution is a risk factor for lower score quality of life, to develop a reference for treatment and preventive strategies.…”
Section: Introductionmentioning
confidence: 99%